Long-term ageing of asphalt mixtures. (27th January 2017) - Yin, Fan; Arámbula-Mercado, Edith; Epps Martin, Amy; Newcomb, David; Tran, Nam
Abstract : Ageing of asphalt mixtures occurs during production and construction and continues throughout the service life of the pavement. Although this topic has been studied extensively, recent changes in asphalt mixture components, production parameters, and plant design have raised a need for a comprehensive evaluation that considers the impacts of climate, aggregate type, recycled materials, WMA technology, plant type, and production temperature. In this study, field cores were acquired from seven field projects at construction and several months afterwards, and raw materials were also collected for fabricating laboratory specimens that were long-term oven aged (LTOA) in accordance with selected protocols. The resilient modulus and Hamburg wheel tracking tests were conducted on both specimen types to evaluate the evolution of mixture stiffness and rutting resistance with ageing. The concepts of cumulative degree days and mixture property ratio were proposed to quantify field ageing and its effect on mixture properties. Test results indicated that the LTOA protocols of two weeks at 140°F (60°C) and five days at 185°F (85°C) produced mixtures with equivalent in-service field ageing of 7–12 months and 12–23 months, respectively, depending on climate. Finally, among the factors investigated in the study, WMA technology, recycled materials, and aggregate absorption exhibited a significant effect on the long-term ageing characteristics of asphalt mixtures, while production temperature and plant type had no effect.